2016
DOI: 10.1159/000447903
|View full text |Cite
|
Sign up to set email alerts
|

Activation of SGK1 in Endometrial Epithelial Cells in Response to PI3K/AKT Inhibition Impairs Embryo Implantation

Abstract: Background: Serum & Glucocorticoid Regulated Kinase 1 (SGK1) plays a fundamental role in ion and solute transport processes in epithelia. In the endometrium, down-regulation of SGK1 during the window of receptivity facilitates embryo implantation whereas expression of a constitutively active mutant in the murine uterus blocks implantation. Methods/Results: Here, we report that treatment of endometrial epithelial cells with specific inhibitors of the phosphoinositide 3-kinase (PI3K)/AKT activity pathway results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…In this study, we showed that Hmgb1 mRNA was obviously observed in uterine epithelium on day 2 and 3 of pregnancy when uterus was pre-receptive, but its expression was scarcely detected with the attainment of uterine receptivity on day 4, which was consistent with that in human and rat uteri [14,22,23], suggesting a potential role of Hmgb1 in preparation for uterine receptivity which was required for successful embryo implantation. With implantation in progress on day 5, the accumulation of Hmgb1 mRNA was distinctly noted in the subluminal stroma surrounding the blastocyst at implantation sites, reinforcing the importance of Hmgb1 in embryo implantation.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we showed that Hmgb1 mRNA was obviously observed in uterine epithelium on day 2 and 3 of pregnancy when uterus was pre-receptive, but its expression was scarcely detected with the attainment of uterine receptivity on day 4, which was consistent with that in human and rat uteri [14,22,23], suggesting a potential role of Hmgb1 in preparation for uterine receptivity which was required for successful embryo implantation. With implantation in progress on day 5, the accumulation of Hmgb1 mRNA was distinctly noted in the subluminal stroma surrounding the blastocyst at implantation sites, reinforcing the importance of Hmgb1 in embryo implantation.…”
Section: Discussionsupporting
confidence: 71%
“…The effect has been attributed in part to sustained increase of cytosolic Ca 2+ activity [47]. The present observation point to 1,25(OH) 2 D 3 sensitivity of the serine/threonine protein kinase AKT which supports cell survival and affects a variety of cellular processes including proliferation, survival, and protein translation [48]. Overexpression of AKT has been correlated with the development and metastasis of various cancers [38].…”
Section: Discussionmentioning
confidence: 70%
“…The following equations (9), (10), (11) and (12) respectively provide C 1 , C 2 , C 3 and C 4 appearing in equations (5), (6), (7) and (8), while l, m or n is one of the three roots, r, of the cubic equation (13) (c.f., Cardano's Formula for cubic equation):…”
Section: Marunaka Et Al: Enac Trafficking and Protein Tyrosine Kinasementioning
confidence: 99%